2021
DOI: 10.2147/ccid.s309681
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Clinical Features of Skin Irritation Caused by Infection Prevention Measures During COVID-19 in the Mecca Region, Saudi Arabia

Abstract: Due to the COVID-19 pandemic, recommendations to prevent infection suggest increasing the frequency of handwashing and disinfection; however, these measures can have negative implications on our skin. This study aims to evaluate whether these measures correlate with new-onset skin damage or can exacerbate hand eczema among the general population. Materials and Methods: This was a descriptive, cross-sectional, survey-based study, including the general population of Mecca region, Saudi Arabia. To achieve the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 15 publications
(34 reference statements)
3
6
2
Order By: Relevance
“…The mean age of doctors participating in the survey was found to be 31.5 years, comparable with the study by Leelawadee et al, 10 where it was 32 years. In our study, males (58.7%) outnumbered females (41.3%) in contrast to previous studies by Leelawadee et al, 10 Guertler et al, 11 Zahr Allayali et al, 12 and Keily et al 13 where there was female predominance due to inclusion of female nurses as HCWs in most of the studies.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The mean age of doctors participating in the survey was found to be 31.5 years, comparable with the study by Leelawadee et al, 10 where it was 32 years. In our study, males (58.7%) outnumbered females (41.3%) in contrast to previous studies by Leelawadee et al, 10 Guertler et al, 11 Zahr Allayali et al, 12 and Keily et al 13 where there was female predominance due to inclusion of female nurses as HCWs in most of the studies.…”
Section: Discussioncontrasting
confidence: 99%
“…The most common symptom in our survey was dryness [60 (42%)], followed by itching [25 (17.5%)]. It is similar to the study by Keily et al, 13 Leelawadee et al, 10 Zahr Allayali et al, 12 Guertler et al, 11 and Agarwal et al 18 It is secondary to depletion of the lipid barrier due to lipid‐emulsifying detergents and lipid‐dissolving alcohols 18 . The most common skin changes seen were scaling in 30 (21%) and redness in 16 (11.2%) doctors, respectively.…”
Section: Discussionsupporting
confidence: 90%
“…The majority ( n = 28, 62.2%) of studies were performed in healthcare workers, 12 (26.7%) were in non‐healthcare workers and five included the general population regardless of occupation. 23 , 26 , 27 , 28 , 29 Outcomes were assessed by self‐reported questionnaire in most studies ( n = 35), of which 12 were based on the NOSQ‐2002 questionnaire, 30 and 10 studies relied on clinical examination by dermatologist or trained professional. Most of the studies were of high quality ( n = 35), and 10 were considered lower quality (NOS < 7).…”
Section: Resultsmentioning
confidence: 99%
“…Numerous individual studies looking into the healthcare and general population separately revealed an increase in the incidence of adverse skin reactions in both groups. 4 , 5 , 6 , 7 , 8 , 9 , 10 In Wuhan (China), 74.5% of health professionals developed hand eczema, with an increased frequency of handwashing as a significant predictor. [ 4 ] Similar studies in Germany, [ 5 ] Turkey, [ 6 ] and India [ 7 ] also revealed a rise in hand eczema reported by healthcare workers at 90.4%, 50.5%, and 65.5% respectively.…”
Section: Introductionmentioning
confidence: 99%
“…24 new cases of hand eczema were diagnosed in urgent care in a study in Milan, [ 8 ] 16 new cases were reported in 10 days in a survey India [ 9 ] and nearly half the participants in a study in Saudi Arabia experienced skin reactions, particularly people those with a history of eczema. [ 10 ] But very limited research was carried out to compare the risks in both the groups side by side. 11 , 12 This study aims to explore these adverse effects within both the groups identify potential risk factors and propose appropriate changes in an attempt to prevent or reduce these effects.…”
Section: Introductionmentioning
confidence: 99%